Characterization of Asphaltene Using Potential Energy and Nanocalculation - Samad Sabbaghi; Abdolhossein Jahanmiri; Shahaboddin Ayatollahi; Mojtaba Shariaty Niassar; Gholam Ali Mansoori (Iranian Journal of Chemistry & Chemical Engineering, 2008)
The basics of quantum mechanics and statistical thermodynamics were used to predict the potential energy and intermolecular forces of asphaltene molecules. The parameters associated with the chemical structure were also estimated for a specific asphaltene molecule to predict the Mie potential function. Based on the structural results, a new form of the Virial EOS with Peneloux correction was developed to estimate the density, solubility parameter and a correction factor that accounts for the structural effect of asphaltene. In this way, asphaltenes were considered as polymer-like compounds consisting of aggregates of a monodisperse. Finally, three new correlations were developed to predict the key parameters of asphaltenes, namely structural coefficient, density and solubility as functions of temperature and molecular weight. The correlations facilitate the calculation of the numerical methods of these parameters. These parameters were also compared successfully with the results found by the Soave Redlich Kwong equation of state. Meanwhile, at first the stage asphaltene was extracted and the roughness of the asphaltene coating in different rpm was studied by using of image analysis confocal microscopy.